2014
DOI: 10.1017/s0022215113003447
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 14-3-3 sigma, cyclin-dependent kinases 2 and 4, p16, and Epstein–Barr nuclear antigen 1 in nasopharyngeal carcinoma

Abstract: Levels of cyclin-dependent kinase 2 and Epstein-Barr nuclear antigen 1 were significantly higher in nasopharyngeal carcinoma than in normal tissue, while p16 gene expression was diminished. These three proteins may contribute to nasopharyngeal carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In addition, it was demonstrated that the protein expression of CDKN2A was significantly decreased in C666-1 cells. Similarly, CDKN2A has been reported to be significantly downregulated in NPC tissues, and frequently methylated in the serum of patients with NPC (31,32). The results of the present study suggested that the decreased expression of CDKN2A may be caused by the upregulation of miR-663 in NPC.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, it was demonstrated that the protein expression of CDKN2A was significantly decreased in C666-1 cells. Similarly, CDKN2A has been reported to be significantly downregulated in NPC tissues, and frequently methylated in the serum of patients with NPC (31,32). The results of the present study suggested that the decreased expression of CDKN2A may be caused by the upregulation of miR-663 in NPC.…”
Section: Discussionsupporting
confidence: 62%
“…Of the seven isoforms, 14-3-3σ is especially linked to cancer. Most of the isoforms are expressed in all tissues, whereas the σ isoform has been restricted to the epithelial cells (Wilker et al 2005;Huang et al 2014). 14-3-3σ is a protein kinase-dependent activator tyrosine and endogenous inhibitor of protein kinase C; it plays a negative role in the G2/M checkpoint, pausing the cell cycle and allowing DNA repair.…”
Section: Research Articlementioning
confidence: 99%
“…This work was supported by the Universidad de Las Palmas de Gran Canaria [grant number VD-IPD 2013-2014.…”
Section: Acknowledgementmentioning
confidence: 99%